2016
DOI: 10.1139/cjfas-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric CO2 interacts with drought and competition to produce complex results in plant quality and subsequent microbial aquatic decomposition

Abstract: Human activities enhance the atmospheric CO 2 concentration and modify climatic patterns, which could change the growth and quality of plant materials, as well as their subsequent decomposition, thus altering stream ecosystem functioning. These effects could be modulated by interactions between plant species differing in biological traits and competitive capacity. We cultivated the forb Trifolium pratense and the grass Agrostis capillaris under different CO 2 concentration (ambient or elevated), water availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, studies that addressed the effects of elevated [CO 2 ] on litter decomposition rates have found contrasting results. Although plants grown under elevated [CO 2 ] were reported to produce slow‐decomposing litter (i.e., higher concentrations of phenolic compounds, condensed tannins, lignin, and C:N; Rier et al, ; Tuchman et al, ) some authors have reported that although phytochemical composition was affected by increases in [CO 2 ], this did not result in measurable changes on litter decomposition rates (Ferreira & Chauvet, ; Martins, Melo, Gonçalves, Campos, & Hamada, ; Monroy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies that addressed the effects of elevated [CO 2 ] on litter decomposition rates have found contrasting results. Although plants grown under elevated [CO 2 ] were reported to produce slow‐decomposing litter (i.e., higher concentrations of phenolic compounds, condensed tannins, lignin, and C:N; Rier et al, ; Tuchman et al, ) some authors have reported that although phytochemical composition was affected by increases in [CO 2 ], this did not result in measurable changes on litter decomposition rates (Ferreira & Chauvet, ; Martins, Melo, Gonçalves, Campos, & Hamada, ; Monroy et al, ).…”
Section: Introductionmentioning
confidence: 99%